Collaboration between designers and facility managers: Comparing the United Kingdom, the United States, and the Middle East. Issue 9 (4th July 2017) - Kalantari, Saleh; Shepley, Mardelle M.; Rybkowski, Zofia K.; Bryant, John A.
Abstract : Purpose: The aim of this study is to focus on the perspectives of facility managers in each region and the different challenges impacting collaboration in each geographical context. This research analyzed obstacles to collaboration between facility managers and architectural designers in three international regions. Design/methodology/approach: A multi-method approach was used, allowing the researchers to triangulate data from in-depth interviews and a widely distributed survey instrument. The participants included a large cross-selection of facility management professionals in each of the regions under study. The interview data were parsed to identify recurring themes, while the survey data were analyzed statistically to test specific hypotheses. Findings: Significant differences were found in the culture of the facility management profession in each region. These differences created unique challenges for collaboration, especially in the context of a non-local design team. While the facility management profession was perceived as most established and professional in the UK, rates of collaboration between facility managers and designers were actually much higher in the USA. Collaborations between facility managers and designers were almost non-existent in the Middle East. Originality/value: While the importance of collaboration between facility managers and designers is increasingly recognized for improving the efficiency of building operations, crucial obstacles continue to limit the scope of this engagement. There has been limited previous research analyzing obstacles to collaboration that are specific to international contexts and non-local design teams. This study helps to fill an important gap in the literature by providing a comparative analysis of collaboration challenges in three international contexts.